2008
DOI: 10.1586/1744666x.4.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms and autoimmune Addison’s disease

Abstract: Autoimmune Addison's disease (AAD) is a complex genetic disease that results from the interaction of a predisposing genetic background with as yet unknown environmental factors. The disease is marked by the appearance of circulating autoantibodies against steroid 21-hydroxylase. Mutations of the autoimmune regulator gene are responsible for the so-called autoimmune polyendocrine syndrome type I (APS I), of which AAD is a major disease component. Among genetic factors for isolated AAD and APS II, a major role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 109 publications
0
14
0
3
Order By: Relevance
“…Genetic predisposition for AAD is modulated by polymorphisms of genes influencing the function of the immune system, such as HLA class II genes, CTLA4, CIITA, PTPN22, and others (10). Though 17OHAb and P450sccAb can be detected in a fraction of patients with AAD, these markers are more frequently present in sera from patients with autoimmune polyendocrine syndrome type 1 (APS1) or in women with adrenal insufficiency and autoimmune oophoritis (1,2,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic predisposition for AAD is modulated by polymorphisms of genes influencing the function of the immune system, such as HLA class II genes, CTLA4, CIITA, PTPN22, and others (10). Though 17OHAb and P450sccAb can be detected in a fraction of patients with AAD, these markers are more frequently present in sera from patients with autoimmune polyendocrine syndrome type 1 (APS1) or in women with adrenal insufficiency and autoimmune oophoritis (1,2,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The CTLA-4 gene polymorphism and the PTPN22 gene polymorphism have been found to modulate genetic risk for AAD (Falorni et al, 2008;Skinningsrud et al, 2008a). A recent metanalysis of European studies has confirmed that the CTLA-4 Ala 17 polymorphism is strongly associated with genetic risk for AAD, independentenly from the well known association with the polymorphism of HLA class II genes (Brozzetti et al, 2010b).…”
Section: Genetics Of Autoimmune Adrenal Insufficiencymentioning
confidence: 89%
“…Outside APS1, AAD shares many predisposing genetic factors with other endocrine autoimmune diseases that are components of APS2, such as thyroid autoimmune diseases and T1DM, the major genetic markers associated with the diseases beeing located in the HLA region on chromosome 6. The disease is strongly and positively associated with both HLA-DRB1*0301-DQA1*0501-DQB1*0201 (DR3-DQ2) and DRB1*04-DQA1*0301-DQB1*0302 (DR4-DQ8) (Falorni et al, 2008). The HLA-DRB1*01-DQA1*01-DQB1*0501 and DRB1*13-DQA1*0103-DQB1*0603 haplotypes are negatively associated with genetic risk for AAD.…”
Section: Genetics Of Autoimmune Adrenal Insufficiencymentioning
confidence: 99%
“…I principali marcatori genetici di predisposizione per lo sviluppo della malattia sono localizzati nella regione HLA, sul cromosoma 6. Infatti, MAA è positivamente associata con HLA-DRB1 * 0301-DQA1 * 0501-DQB1 * 0201 (DR3-DQ2) e DRB1 * 04-DQA1 * 0301-DQB1 * 0302 (DR4-DQ8) [22]. HLA-DRB1 * 01-DQA1 * 01-DQB1 * 0501 e DRB1 * 13-DQA1 * 0103-DQB1 * 0603 sono invece negativamente associati con lo sviluppo di MAA.…”
Section: Fisiopatologia Del Morbo DI Addison Autoimmune Isolato E Delunclassified
“…Tra i geni non-HLA, i polimorfismi di CTLA-4 e di PTPN22 contribuiscono al rischio per lo sviluppo di MAA e di altre malattie endocrine autoimmuni [22,[28][29][30]. Due studi europei indipendenti hanno documentato l'associazione del gene del transattivatore delle molecole HLA di classe II (CIITA, MHC2TA) con MAA [31,32].…”
Section: Fisiopatologia Del Morbo DI Addison Autoimmune Isolato E Delunclassified